Relevance of Ambedkar's ideology - Kanta Kataria (Rawat Publications, 2015)
Secularisation of Indian Mind is meant for amateurs and students of different streams and is an attempt to help them realise the line of development and changes that occurred to secularise the Indian mind. The main objective will be accomplished only if the present generation after going through this book will start taking pride in the rich cultural heritage that our country possesses. The book tries to find the answer to the million-dollar question, "What is the real meaning of secularisation?", and further traces its progress through different realms of Indian society, thereby meeting the requirement of both amateur and intellect to an equal degree."